The Development Of Helth Belief In Children - Mahdi, Intisar Hashem (Al-Adab Journal, 2020)
The study aimed to identifyhealth belief in children aged (6.7, 9, 11) years.Know the differences in the health belief among respondents according to age(6.7, 9, 11) years.Know the differences in the health belief among respondents according to gender (male and female).Find the current sample included( 160) boys and girls in the city of Baghdad from primary school, has prepared a( 24-Item) to measure the health belief adopted a definition of the researcher (Ajzen,1991) and his theory in the preparation of the paragraphs and extracted researcher psychometric properties of the scale. The study came out the existence of a healthy belief in children aged 6 years and the existence of an evolutionary path of progress in the development of the health belief in children. And the existence of differences in the health belief according to gender in favor of Male.